2012
DOI: 10.1364/ol.37.002907
|View full text |Cite
|
Sign up to set email alerts
|

Optical field enhancement in nanoscale slot waveguides of hyperbolic metamaterials

Abstract: Nanoscale slot waveguides of hyperbolic metamaterials are proposed and demonstrated for achieving large optical field enhancement. The dependence of the enhanced electric field within the air slot on waveguide mode coupling and permittivity tensors of hyperbolic metamaterials is analyzed both numerically and analytically. Optical intensity in the metamaterial slot waveguide can be more than 25 times stronger than that in a conventional silicon slot waveguide, due to tight optical mode confinement enabled by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…1 shows the schematic of the proposed HM slot waveguides. Two identical HM waveguides composed of alternating metal-dielectric multi layers [25,26] with a square cross section of 250 nm × 250 nm are placed adjacent to the both sides of a nonlinear organic polymer in the slot (height g = 20 nm). The assumed polymer is a doped, cross-linked organic polymer with a nonlinear susceptibility of χ (2) 111 = 619 pm/V [15,27] and refractive index n = 1.68 at the wavelength of λ = 1,550 nm (n = 1.58 at λ 3,100 nm) [24].…”
Section: Waveguide Structurementioning
confidence: 99%
See 3 more Smart Citations
“…1 shows the schematic of the proposed HM slot waveguides. Two identical HM waveguides composed of alternating metal-dielectric multi layers [25,26] with a square cross section of 250 nm × 250 nm are placed adjacent to the both sides of a nonlinear organic polymer in the slot (height g = 20 nm). The assumed polymer is a doped, cross-linked organic polymer with a nonlinear susceptibility of χ (2) 111 = 619 pm/V [15,27] and refractive index n = 1.68 at the wavelength of λ = 1,550 nm (n = 1.58 at λ 3,100 nm) [24].…”
Section: Waveguide Structurementioning
confidence: 99%
“…The hyperbolic metamaterials were composed by alternate thin layers of silver (Ag, filling ratio f r ) and germanium (Ge) with a pitch thickness of 10 nm [24]. The metamaterial can be treated as a homogeneous effective medium [25,26]. The linear modal properties taking into the nonlinear coupling wave equations are the complex effective index and the field distribution in the slot.…”
Section: Waveguide Structurementioning
confidence: 99%
See 2 more Smart Citations
“…HMMs have been investigated for potential applications in negative refraction, 2,3 imaging hyperlens, 4 and as an optical waveguide. 5 HMMs exhibit exotic physical behavior such as the broadband Purcell effect, 6 nonlinear effect, 7 and perfect absorption. 8,9 Smolyaninov 10 found that HMMs display critical opalescence, indicating that they may emulate virtual microscopic black holes, an interesting feature of the real physical space-time.…”
Section: Introductionmentioning
confidence: 99%